Modeling of atmospherically important vapor-to-particle reactions - Hashmi, Bahaudin, author; Shipman, Patrick, advisor; Liu, Jiangguo, advisor; Thompson, Stephen, committee member (Colorado State University. Libraries, 2014)
Liesegang ring formation is a special type of chemical pattern formation in which a spatial order is formed by density fluctuations of a weakly soluble salt. The Vapor-to-Particle nucleation process that is believed to produce these Liesegang rings is theorized to be the cause of mini-tornadoes and mini-hurricanes developed in a lab. In this thesis, we develop a one-dimensional finite element scheme for modeling laboratory experiments in which ammonia and hydrogen chloride vapor sources are presented to either end of the tubes. In these experiments, a reaction zone develops and propagates along the tube. Both numerical simulations and the laboratory experiments find an increasing amplitude of oscillations at the reaction front.
Keywords: finite element scheme; vapor-to-particle reaction; nucleation